Development of the BCELM Learning Model: An R&D Study on Enhancing Critical and Creative Thinking in Madrasah Ibtidaiyah - Muhamad Azhar Alwahid; M. Zainul Hasani Syarif; Khoridah Afifah; Agus Suryana; Akalia Akalia (LP. Ma'arif Janggan Magetan, 2026)
This study aimed to develop and evaluate the effectiveness of the Brain-Friendly, Child-Friendly, and Environmentally-Friendly Learning Model (BCELM) in enhancing students’ critical and creative thinking in Islamic Religious Education (PAI) at Madrasah Ibtidaiyah. The study employed a Research and Development (R&D) approach using the Dick and Carey instructional design model. A preliminary needs analysis was conducted with 22 students, followed by a small-class trial involving 24 students and an expanded implementation involving 64 students at MI An-Nizhomiyah Depok. Data were collected through expert validation, classroom observations, critical and creative thinking assessments, and statistical analysis. The findings indicate that BCELM is valid, feasible, and effective for classroom implementation. Regression analysis showed that BCELM had a significant positive effect on students’ critical and creative thinking patterns (Sig. = 0.002 < 0.05). In addition, the model improved students’ learning engagement, including their interest, attention, participation, and attendance. These findings demonstrate that BCELM provides an effective instructional approach for fostering higher-order thinking skills and improving learning engagement in Madrasah Ibtidaiyah.